How does the expert diversity in GraphMETRO affect downstream task performance on VQAv2 and GQA benchmarks und - Assignee Research (Assignee Research, 2026)
Graph data are inherently complex and heterogeneous, leading to a high natural diversity of distributional shifts. However, it remains unclear how to build machine learning architectures that generalize to the complex distributional shifts naturally occurring in the real world. Here, we develop GraphMETRO, a Graph Neural Network architecture that models natural diversity and captures complex distributional shifts. GraphMETRO employs a Mixture-of-Experts (MoE) architecture with a gating model and
Machine-generated literature synthesis.